Prevalence of vitamin D deficiency in patients with sickle cell disease in Bahrain - Bakri, Adla H; Garadah, Taysir S; jaradat, ahmed A; Al Ajmi, Abdulla; Alawi, Mohamed E; Sequeira, Reggy R (International Journal of Medicine, 2013)
Background: Patients with sickle cell disease (SCD) had a low serum level of vitamin D. The magnitude of this observational finding is neither clear in patients in Bahrain, nor its impact on the disease process.Aim: To assess the prevalence of vitamin D deficiency (VDD) in homozygous patients with SCD, and to evaluate the clinical and biochemical predictors of occurrence of VDD in such patients.Methods: We evaluated the vitamin D status in 70 patients with confirmed diagnosis of SCD and compared them with an age matched control group. Serum level of vitamin D, parathormone (PTH), calcium, phosphate, alkaline phosphatase, haemoglobin (Hb), and uric acid were measured. Linear regression analysis was performed to assess the relation between PTH and vitamin D level. Multiple regression analysis was performed to assess the predictive value of gender, age (>18 years), body mass index (BMI), serum level of uric acid and estimated glomerular filtration rate (eGFR) for vitamin D deficiency in patients with SCD.Results: The mean age of the study group was 28.85 ±7.21 years compared with the control of 29.91 ±4.3 years, p=0.23. There were 40 (57%) female SCD patients compared with 39 (55%) in the control. In patients with SCD, the serum level of vitamin D was sufficient, >50 nmol/L in 4 (5%) patients, insufficient > 27.5 - ?50 nmol/L in 21 (30%) patients, deficient >12.5 - ?27.5 nmol/L 35 (50%) and profoundly deficient ?12.5 nmol/L in 10(15%). In the control group those with sufficient level of vitamin D were 53 (75%), insufficient 21(30%) deficient of 10 (15%) and none with profound deficiency, respectively. The serum level of PTH in the SCD group compared with control group was 6.92 ±0.6 pmol/L vs. 4.13±0.34 p mol/L (p<0.001), the serum level of alkaline phosphatase was 190.7 ±78 U/L vs. 41.03 ±12.78 (p<0.001), respectively. In SCD patients compared with normal population had significantly lower eGFR of 67.3 ±7.8 vs. 92.5 ±63.94, Hb of 8.9 ±0.8 vs. 13.01 ±1.12 gm/dl and bpm of 19.5 ±2.4 vs. 24.04 ±2.86. The serum level of uric acid was significantly higher (p < 0.05). Patients with SCD had higher heart rate of 80 vs. 70 bpm (p<0.001). There was no significant difference between serum level of calcium or phosphate. Linear regression analysis showed inverse relation between VDD (<25 nmol/L) and PTH (r = - 0.34, P<0.001). Multiple regression analysis showed female gender and age >18 years as positive predictors of VDD in SCD with odds ratio for female gender of 2.2 (95% CI: 1.8-2.6, P <0.05) , BMI >24 of 1.2(95%CI:0.8-1.6,P=0.02 ) and hyperuercemia >400 mg/L 1.0 (95%CI:0.8-1.2,P<0.04) , low eGFR (<60) of 0.8(95%CI: 0.7-0.9,P<0.045) and , age (>18 years) was of no significant predictive value.Conclusion: The risk of vitamin D deficiency among subjects with SCD-SS was 3.8 folds greater than control subjects; the prevalence of VDD in SCD was 95% and 25% in the control patients without SCD. On linear regression analysis, there is a significant inverse relation between serum levels of vitamin D and PTH in SCD patients. The female gender, BMI>24, hyperurecemia and low eGFR were positive predictor of VDD in patients with SCD.